Differential regulation of synaptic vesicle proteins by antidepressant drugs - Britsch, Simone; Baader, M.; Hu, M.; Jennen-Steinmetz, Christine; Henn, Fritz A.; Thome, Johannes (The pharmacogenomics journal, 2004)
Synaptic vesicle proteins (SVP) play a critical role in neurotransmitter release and neural plasticity, and have been implicated in the pathophysiology of psychiatric disorders such as depression. Antidepressant drugs not only alter the level of neurotransmitters, but also modulate de novo gene transcription and synthesis of proteins involved in neural plasticity. In order to investigate the effects of antidepressant compounds on SVP-mRNA levels, the expressions of synaptophysin, synaptotagmin, VAMP, and synapsin-I were analysed by in situ hybridization in rats which had been treated with desipramine, fluoxetine, tranylcypromine, or saline. The results demonstrate that chronic treatment with fluoxetine and tranylcypromine leads to an increased expression of synaptophysin, but decreased expression of synaptotagmin and VAMP in the hippocampus and cerebral cortex. Additionally, synapsin I-mRNA levels in the hippocampus and cerebral cortex are significantly reduced in tranylcypromine-treated animals. This identifies SVP genes as target genes of antidepressant treatment.